2022
DOI: 10.3390/su142416654
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Causes of Traffic Crashes Associated with Driver Behavior Using Supervised Machine Learning Methods: Case of Highway 15 in Saudi Arabia

Abstract: Identifying the causes of road traffic crashes (RTCs) and contributing factors is of utmost importance for developing sustainable road network plans and urban transport management. Driver-related factors are the leading causes of RTCs, and speed is claimed to be a major contributor to crash occurrences. The results reported in the literature are mixed regarding speed-crash occurrence causality on rural and urban roads. Even though recent studies shed some light on factors and the direction of effects, knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
(143 reference statements)
1
0
0
Order By: Relevance
“…Two-wheelers, in particular, account for 25% of all road crash deaths. The road features and traffic flow parameters leading to RTCs associated with driver errors along an access-controlled major highway in Saudi Arabia and the results supported previous studies in comparison with the similar study contexts that looked at speed dispersion in crash occurrence and severity (11) .…”
Section: Background Worksupporting
confidence: 85%
“…Two-wheelers, in particular, account for 25% of all road crash deaths. The road features and traffic flow parameters leading to RTCs associated with driver errors along an access-controlled major highway in Saudi Arabia and the results supported previous studies in comparison with the similar study contexts that looked at speed dispersion in crash occurrence and severity (11) .…”
Section: Background Worksupporting
confidence: 85%
“…Each decision tree in the random forest is associated with a subset of the dataset itself. The k-nearest neighbor algorithm can be used for classification, such that the output of a specific input is the output majority of its neighboring inputs [28]. The value of k can be set to any integer but is usually optimized depending on the dataset.…”
Section: Lighting Design Predictionmentioning
confidence: 99%
“…Recent studies have shown that machine learning and classification algorithms can effectively predict traffic crashes. For instance, a study by Akin et al [65] used supervised machine learning techniques such as binomial logistic regression and other models to forecast the likelihood of traffic crashes involving driver error on a major highway. According to the study, the possibility of crashes caused by driver mistakes dropped as the number of lanes and daily average speed of traffic flow increased.…”
Section: Predicting Future Crash Involvementmentioning
confidence: 99%